Knowledge and Attitudes Related to Health Seeking Behavior of Communities in Developing Countries Towards Tuberculosis (TB) Disease - Ramadhani, Rima Putri; Sophy Wulandari; Indah Laily Hilmi (CV. CENDIKIA JENIUS INDONESIA, 2025)
A person with tuberculosis may experience disease severity due to a lack of knowledge about tuberculosis, gender, place of residence, occupation, education level, and age. These factors influence knowledge and attitudes related to health-seeking behavior in communities of developing countries. The aim of this study is to explore knowledge, attitudes, and health-seeking behavior among people in developing countries.Methods: This study used an observational method with a literature review approach. The data sources used in this literature review were the PubMed and Scopus databases. Results: From the literature review, eight articles were identified and analyzed based on inclusion and exclusion criteria. The results showed that factors associated with knowledge and attitudes toward health-seeking behavior among people with tuberculosis in developing countries include lack of knowledge about the disease, gender, place of residence, age, education level, and occupation. Conclusion: Knowledge about tuberculosis significantly influences community attitudes and behavior in seeking appropriate healthcare services. Recommendation Future researchers should expand data coverage and provide education about TB to improve the accuracy and usefulness of the research.